The Rapprochement of Literary Armenian Varieties:Manuk Abeghian’s Approach and Contemporary Manifestations - Poghosyan, Norayr (Bulletin of Yerevan University B: Philology, 2026)
The following article examines both earlier and more recent proposals concerning the rapprochement of the two branches of Modern Armenian, tracing these ideas from the nineteenth century to the present. Particular attention is devoted to the approaches of Nahapet Rusinian and Step‘an Palasanian, while special emphasis is placed on the analysis of Manuk Abeghian’s influential article and the positions articulated therein. The process of standardization and the expansion of general usage of the two branches of Modern Armenian have consistently been accompanied by debates over their regulation and the clarification of their boundaries in relation to Classical Armenian. Publications addressing this issue have repeatedly advanced ideas of rapprochement and, in some cases, even unification of the two branches, both within Western and Eastern Armenian contexts. Manuk Abeghian’s programmatic article is especially significant in this respect, as it proposes a set of clearly formulated measures aimed at bringing the two branches of the language as close as possible to one another, emphasizing not only their linguistic and national importance, but also their broader social and economic implications. Various approaches to the selection of grammatical forms, lexical usage, and syntactic structures are proposed and critically discussed. Abeghian’s contribution to this linguistic and literary movement is further evidenced in his article “The Problem of the Unity of Our Two Literary Languages.” The second part of the article presents concrete examples drawn from the Armenian-American milieu, demonstrating that proposals advanced since the mid-nineteenth century have, to a certain extent, found practical realization in contemporary usage. In the American context, the two branches of Armenian, developing with a degree of autonomy, acquire lexical, syntactic, and phonological features that differ from both Eastern and Western Armenian. These features emerge as a result of mutual interaction between the two branches as well as their relatively equal exposure to the influence of English.